Meningkatkan pukulan drive pemain tenis pemula melalui metode pelatihan berbasis koordinasi tangan-mata - Nur, Muhammad; Mappaompo, M. Adam; Juhanis, Juhanis; Awal, Asri; Purwanto, Didik (Universitas Nusantara PGRI Kediri, 2024)
The mastery of skills by field tennis players is very important. To master the skills, novice players must practice a lot. In the training process, the right training method is needed so that beginner players can master mastery of field tennis skills such as drive strokes. This study aimed to determine the effectiveness of training methods with hand-eye coordination in improving field tennis drive skills. This study used an experimental method with a 2x3 factorial research design. This study used a purposive sampling technique, so the number of subjects obtained was 60. The research instrument used the Dyer tennis test to determine the skill of field tennis drive shots. Analysis of research data Data analysis in this study used a prerequisite test with Sig> α0.05 and hypothesis testing using the two-way ANOVA test. The results showed that the sig value was 0.004 <0.05, so there was a difference in the effect of training methods in improving field tennis drive shots. It can be concluded that the paired training method is better, with an average value of 45.6, compared to the training method of the ball bounce machine against the wall, and the training method with a thrower, with an average value of 41.3 and 38.7.